Analysis of the Network Communication Approach to Public Diplomacy: Case Study of the Confucius Institute at Carleton University - Shi, Lu (Université d'Ottawa | University of Ottawa, 2015)
Since 2004, China has set up over 450 Confucius Institutes to promote its language and culture and thereby, to shape its image. The Confucius Institutes have been seen as a highly networked public diplomacy initiative, and appear to adopt a relational rather than an information framework. This research paper studies the Confucius Institute at Carleton University (CICU) and applies the network communication approach to test whether the CICU conforms to tenets of Zaharna’s relational framework of public diplomacy. The research paper’s findings offer a concrete model for building a network-based cultural institute.